The diploic venous system in Homo neanderthalensis and fossil Homo sapiens: A study using high‐resolution computed tomography - (:unkn) unknown (My University, 2023)
Objectives: The diploic venous system has been hypothesized to be related to human brain evolution, though its evolutionary trajectory and physiological functions remain largely unclear. This study examines the characteristics of the diploic venous channels (DCs) in a selection of well-preserved Homo neanderthalensis and Upper Paleolithic Homo sapiens crania, searching for the differences between the two taxa and exploring the associations between brain anatomy and DCs. Materials and Methods: Five H. neanderthalensis and four H. sapiens fossil specimens from Western Europe were analyzed. Based on Micro-CT scanning and 3D reconstruction, the distribution pattern and draining orifices of the DCs were inspected qualitatively. The size of the DCs was quantified by volume calculation, and the degree of complexity was quantified by fractal analyses. Results: High-resolution data show the details of the DC structures not documented in previous studies. H. neanderthalensis and H. sapiens specimens share substantial similarities in the DCs. The noticeable differences between the two samples manifest in the connecting points surrounding the frontal sinuses, parietal foramina, and asterional area. Discussion: This study provides a better understanding of the anatomy of the DCs in H. neanderthalensis and H. sapiens. The connection patterns of the DCs have potential utility in distinguishing between the two taxa and in the phylogenetic and taxonomic discussion of the Neandertal-like specimens with controversial taxonomic status. K E Y W O R D S brain evolution, craniovascular system, fossil hominins, micro-CT Research Highlights • Micro-CT reveals the undiscovered draining orifices in fossils. • H. sapiens specimens do not display more developed diploic venous networks compared with H. neanderthalensis sample. • The diploic veins have potential utility in taxonomic analyses.
Keywords: African Research